A Cephalometric Comparison of Pharynx and Soft Palate in Iraqi Adolescents and Adults Population - Nada M Al-Sayagh (University of Mosul, College of Dentistry, 2012)
Aims: This paper aims to estimate and compare the pharynx and soft palatal dimensions of Iraqi ado-lescent and adults with class I normal occlusion at Mosul City and to identify any gender dimorphism within each group. Materials and Methods: Lateral cephalometric radiographs of 160 normal Iraqis what were separated into two groups (80 adolescents and 80 adults). Each group was additionallydi-vided into two subgroups according to gender (40 of each gender). Twelve linear measurements were made in all subjects; gender dimorphism and comparison between two age groups were analysed by students t test.Results:No gender differences in all variables except in retropalatal airway space (U-MPW) in the adolescents group. While, in the adults the only significant gender differences were found in the thickness of posterior nasopharyngeal wall (ad1-Ba)and in the vertical airway space (Pm-Eb).The adults had significantly larger values for superior nasopharyngeal(pm-ad2) and inferior naso-pharyngeal depth (pm-ad1) than adolescents .While ,adolescents had larger value for superior nasopha-ryngeal thickness (ad2-s) and posterior nasopharyngeal thickness(ad1-Ba) than adults in both genders .The adult male had a higher value for (Pm-Eb) than adolescent male .While ,adolescent female had a higher value for soft palate thickness (SPT) than adult female. Conclusions: Data derived from this study should be a useful reference for assessment of sleep apnea and other conditions in the Iraqi popu-lation.Developmental changes were found in all nasopharyngeal parameters except the Pm-ba(sagittal depth of the bony nasopharynx).